More than just collateral damage. Ramifications of the pandemic for freedom of the press - Holtz-Bacha, Christina (Publizistik: Vierteljahreshefte für Kommunikationsforschung, 2022)
Confronted with a situation that was new to everyone, world leaders sought the best way to contain the pandemic caused by the coronavirus. The measures introduced, with lockdowns and curfews, affected fundamental rights such as freedom of movement and assembly, with implications for freedom of expression and freedom of the press. Demonstrations against the governments’ COVID-19 policies and the associated encroachments on citizens’ fundamental rights in turn led to attacks on media representatives and thus on the freedom of reporting. They were also further proof that attacks on the freedom of the media no longer come only from the state. The restrictions on journalistic work were by no means a surprise attack on the media, but the continuation of a worldwide trend that has been evident for several years, not only in authoritarian systems, but also in established democracies. For those who fear the free press and its watchdog function, the pandemic provided a welcome opportunity, under the pretext of public health, to tighten the reins a bit more and create facts that will endure beyond the pandemic. Financial support for the media, especially the printed press, to cushion the economic consequences of the pandemic and to secure newspapers for the future, establishes new dependencies that can affect free reporting in the long term.<br